2011
DOI: 10.5402/2011/714947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-month, Multimodal Exercise Program on Clinical and Gait Parameters of Patients with Idiopathic Parkinson's Disease: A Pilot Study

Abstract: This pilot study aimed to identify the effects of a 6-month, multimodal exercise program on clinical and gait parameters in patients with Parkinson's disease. Two groups of participants were enrolled in the study: Trained Group (TG) and Control Group (CG). Individuals in the TG exercised three times a week for 24 weeks (in a multimodal exercise program), while the CG participants maintained their regular activity level. Participants in both the TG and the CG were assessed at pre- and posttest by clinical rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 32 publications
2
19
1
9
Order By: Relevance
“…In general, the results confirmed the hypothesis of the study, indicating that after eight months of physical exercises there is an improvement in the articular range of motion in patients with PD. This finding corroborates studies which verified the effect of long-term physical exercises 6,8,11 , indicating that the physical exercise is important in controlling the progression of PD. However, the effect of physical exercises on articular range of motion seems not to be influenced by gender and by the severity of the PD, indicating that the effects are independent from these aspects.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In general, the results confirmed the hypothesis of the study, indicating that after eight months of physical exercises there is an improvement in the articular range of motion in patients with PD. This finding corroborates studies which verified the effect of long-term physical exercises 6,8,11 , indicating that the physical exercise is important in controlling the progression of PD. However, the effect of physical exercises on articular range of motion seems not to be influenced by gender and by the severity of the PD, indicating that the effects are independent from these aspects.…”
Section: Discussionsupporting
confidence: 91%
“…The improvement in the articular range of motion of ankle dorsiflexion may lead to greater control of the movement, especially in gait in order to absorb the load during walking and in posture for balance control, benefiting patients in their mobility 29 . Furthermore, the exercises were able to reverse the progression of the PD, which tends to increase in around 10% a year 26 , as indicated by the maintenance of the clinical parameters and confirming previous studies 6 . With this, it may be suggested that the severity and progression of the proposed physical exercise program were appropriated in order to improve the articular range of motion and to control the progression of the PD.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this way, the advantages of a multimodal long-lasting training program include: beyond the advantages of specific methods (improvement of strength, flexibility, coordination, etc.) these programs are also focused on patients' motor impairments; they have a high adherence; are feasible; promote an active-life style for more lasting time [10,[19][20][21]. Indeed our group had already been successful to demonstrate the benefits of long-lasting training program in gait parameters, executive functions, and balance [10,[19][20][21].…”
Section: Introductionmentioning
confidence: 83%